Evaluasi Usability Sistem Informasi Sitabah Tanggap Bencana dan Musibah Menggunakan Metode System Usability Scale (SUS) - Ramadhan, R. Muchamad Naufal (Yayasan Pendidikan Tanggui Baimbaian, 2024)
Sumedang Regency BPBD Disaster Response Information System (SITABAH) is a platform that manages information and data related to disaster management. Usability evaluation is important to ensure the system is effective and efficient for users. This research aims to measure the level of usability of the SITABAH website using the System Usability Scale (SUS) method and provide recommendations for improvement. Testing involved 96 respondents who used SITABAH. Data is collected through a validated SUS questionnaire and analyzed to obtain a SUS score which indicates the level of system usability. The research results show that the total SUS score from 96 respondents is 6755, with an average score of 70.3 which is rounded to 70. Based on the SUS grade scale, a score of 70 is grade C, indicating an average level of usefulness. On an adjective scale, this score is categorized as “OK,” indicating that the user is quite comfortable using the system. According to the acceptability scale, a score of 70 falls into the category of “marginally acceptable.” Recommended improvements include simplifying the user interface, adding clearer usage guides, and improving features to make things easier for new users. Implementation of these recommendations is expected to increase comfort and ease of use of the SITABAH information system.